Right Temporoparietal Junction Plays a Role in the Modulation of Emotional Mimicry by Group Membership - Peng, Shenli; Kuang, Beibei; Zhang, Ling; Hu, Ping (Frontiers in Human Neuroscience, 2021)
Our prior research demonstrated the right temporoparietal junction (rTPJ) exerted a modulatory role in ingroup bias in emotional mimicry (Peng et al., 2020). In this study, two experiments were conducted to further explore whether the rTPJ is a neural region for emotional mimicry or for the modulation of emotional mimicry by group membership. Both experiments employed noninvasive tDCS technique to temporarily change the cortical excitability over the rTPJ, and facial electromyography (fEMG) to measure facial muscle activations as index of emotional mimicry. After the anodal or sham stimulation, participants in Experiment 1 passively viewed a serial of happy emotional clips while another group of participants in Experiment 2 viewed happy clips performed by ethnic ingroup and outgroup models. fEMG analyses revealed participants in Experiment 1 showed the same degree of happy mimicry for both tDCS conditions (anodal vs. sham), and participants in Experiment 2 showed an ingroup bias in happy mimicry in the sham condition, which disappeared in the anodal condition. Taken together, the present study demonstrated rTPJ plays a role in the modulation of emotional mimicry by group membership.